Impact of COVID-19 and COVID-19 vaccination on high-risk patients with antiphospholipid syndrome: a nationwide survey. Issue Volume 61:Issue S12(2020) (12th April 2022) - Pengo, Vittorio; Del Ross, Teresa; Tonello, Marta; Andreoli, Laura; Tincani, Angela; Gresele, Paolo; Silvestri, Elena; Simioni, Paolo; Campello, Elena; Hoxha, Ariela; Falanga, Anna; Ghirarduzzi, Angelo; et al.
Abstract: Objectives: Patients with APS and triple-positive for aPL are at high risk of recurrent events. As COVID-19 and COVID-19 vaccination may induce thrombotic complications, the objective of the study was to assess the course of COVID-19 and adverse events after vaccination in these patients. Methods: This is a nationwide multicentre survey conducted in nine APS referral centres by means of a questionnaire. Included patients are thrombotic APS with triple-positive aPL confirmed 12 weeks apart. Reference specialist physicians used a four-graded scale of severity for COVID-19 [from 0 (asymptomatic) to 3 (hospitalization in intensive care unit)] and a six-graded scale for adverse reactions to vaccination [from 0 (transient local injection site sign/symptoms) to 5 (potentially life-threatening reactions)]. Outcomes were considered within a 30-day period. Results: Out of 161 patients interviewed, 18 (11%) had COVID-19. All of them fully recovered without any progression to severe disease nor thromboembolic event. A total of 146 patients received the first (92%) and 129 (80%) the second dose of vaccine; side effects were minimal and, in most cases (83% after the first and 68% after the second vaccination) limited to a sore arm. Fifteen patients (9%) were unvaccinated. Most of them raised doubts on the need for vaccination, complained of poor safety and in general were reluctant about COVID-19 vaccination. Conclusion: Patients with triple-positive thrombotic APS did not suffer from severe COVID-19 outcomes. Importantly, COVID-19 vaccination was well tolerated. These data may reassure patients and physicians and contribute to reducing hesitancy in unvaccinated patients.